The post-award effort of managing and reporting on funded research: a scoping review [version 2; peer review: 2 approved] - Amanda Blatch-Jones; Kathryn Fackrell; Ksenia Crane (F1000Research, 2023)
Introduction: Reporting on research is a standard requirement of post-award management, and is increasingly required for ‘compliance’ and to show the impact of funding decisions. The demand for information on research is growing, however, approaches in reporting and post-award management appear inconsistent. Altogether, this can lead to perception of unnecessary effort and ineffiency that impacts on research activity. Identifying this effort is crucial if organisations and Higher Education Institutions (HEIs) are to better streamline and support on their processes. Here, we review the ‘effort’ and processes in post-award management, explore current practices and the purposes of reporting on research. We also identify where effort is perceived as unnecessary or improvements are needed, using previous reports of solutions to inform recommendations for funders and HEIs.  Methods: We conducted a scoping review of the relevant research and grey literature. Electronic searches of databases, and manual searches of journals and funder websites, resulted in inclusion of 52 records and 11 websites. Information on HEI and funder post-award management processes was extracted, catalogued, and summarised to inform discussion.  Results: Post-award management is a complex process that serves many purposes but requires considerable effort, particularly in the set up and reporting of research. Perceptions of unnecessary effort stem from inefficiencies in compliance, data management and reporting approaches, and there is evidence of needed improvement in mechanisms of administrative support, research impact assessment, monitoring, and evaluation. Solutions should focus on integrating digital systems to reduce duplication, streamlining reporting methods, and improving administrative resources in HEIs.  Conclusions: Funders and HEIs should work together to support a more efficient post-award management process. The value of research information, and how it is collected and used, can be improved by aligning practices and addressing the specific issues highlighted in this review.